Orthodox Christianity and the COVID-19 pandemic - Metreveli, Tornike (London New York Routledge, Taylor & Francis Group, 2024)
"This book probes into the dynamics between Orthodox Christianity and the COVID-19 pandemic, unraveling a profound transformation at institutional and grassroots levels. Employing a multidisciplinary approach, and drawing upon varied data sources, including surveys, digital ethnography, and process tracing, it presents unprecedented insights into church-state relations, religious practices, and theological traditions during this crisis. Chapters analyze divergent responses across countries, underscore religious-political interplay, and expose tensions between formal and informal power networks. Through case studies, the book highlights the innovative adaptability within the faith, demonstrated by new religious practices and the active role of local priests in responding to the pandemic. It critically examines how the actions of religious and political figures influenced public health outcomes. Offering a fresh perspective, the book suggests that the pandemic may have permanently influenced the relationship between Orthodox Christianity, public health, and society"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: COVID-19 Pandemic, 2020- -- Religious aspects -- Orthodox Eastern Church; COVID-19 Pandemic, 2020- -- Europe, Eastern; COVID-19 Pandemic, 2020-2023 -- Religious aspects -- Orthodox Eastern Church; COVID-19 Pandemic, 2020-2023 -- Europe, Eastern; Aufsatzsammlung